2019
DOI: 10.11591/ijeecs.v13.i1.pp15-21
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of accessing learning management system among students

Abstract: <p>Learning Management System (LMS) is an online software that was hosted on a server and designed specifically to manage learners’ information, course registration, learning content, and assessment tool. Educational data mining is a way of evaluating and using methods for examining the unique and large dataset that come from educational field, and applying those in order to understand how students learn and the settings in which they learn. Many students use to miss some of the activities posted by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results of Table 4, show that there is a strong and significant relationship of 0.956, between the qualification of the global indicator of teacher performance and the satisfaction of the class administration. In his research [35], comes to the conclusion that a good grade by students towards the teacher is due to being satisfied with the following factors: timely and quality feedback, order (discipline, responsibility, punctuality and coherence between the activities and the course program). The Table 5 shows the results of the correlation of the global indicator of teacher performance (IGD1) with the IED5 indicator.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Table 4, show that there is a strong and significant relationship of 0.956, between the qualification of the global indicator of teacher performance and the satisfaction of the class administration. In his research [35], comes to the conclusion that a good grade by students towards the teacher is due to being satisfied with the following factors: timely and quality feedback, order (discipline, responsibility, punctuality and coherence between the activities and the course program). The Table 5 shows the results of the correlation of the global indicator of teacher performance (IGD1) with the IED5 indicator.…”
Section: Resultsmentioning
confidence: 99%
“…An LMS is a web-based VLE that is hosted on cloud or a server that enables instructors and learners to interact together and provide an avenue for students to interact with each other, with learning contents and actively learn on their own [26]. LMS allows a virtual classroom interaction between students and between students and their teachers [27]. It is used to manage and deliver instructional contents and to monitor the learning process and pace of each individual learner [28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study program will obtain a value that is not optimal in the study program accreditation process. [2] This study proposes a classification model that can be used to predict student study periods using the Naive Bayes Classifier and C4.5 algorithms. Based on previous research, both of them showed quite a high accuracy [3][4][5] [6].…”
Section: Introductionmentioning
confidence: 99%